Enhanced performance of Automatic Single-axis Solar Tracking system fed Induction Motor Drive (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Nowadays Nonconventional Energy sources got vital Role to meet the increase in energy demand because of depletion of fossil fuels. This paper is to design and construct a solar tracker system increases the electricity generation that follows the Sun direction because the continuous movement of the sun limits maximum sun light irradiation absorption.   The proposed system is simple and low-cost price solar tracker system with single axis.UAisingleiaxisitrackericaniincreaseiproductionibetween 25%ito 35%. The proposed systemidevelopsiwith PIC microcontroller, LDR’s are used to detect the Sun direction.gTheioperationiofithe experimentalzmodelgofkthekdeviceaisptoxdrivewInductionumotorxintelligentlyacontrolledpbybakdedicatedcdrivehunitkthatmovesdaoPVzpanelpaccordingstouthexsignalsmreceivedpfromztwowsimplenbutwefficientblightfsensors.nIt runs a single-phase induction motor through an Inverter circuit. The main aim of this paper is that it compares the power produced with and without solar tracker at some maximum point in different temperature conditions.